Analysing Cybernetic Governance at Higher Education Institutions in Malaysia: How is Co- Production Linked to the Transformation of Higher Education Institutions via Governance? (Journal of Governance and Development (JGD), 2020)
This paper attempts to analyse how important the cybernetic governance is to higher education institutions in Malaysia. Cybernetic governance is a structure, process of a system to empower greater decision making, autonomy, leadership, and greater accountability. Thus, cybernetic approach is heavily depending on information, utilise information for decision making, policy making and feedback to respond effectively. The concept also relevant with co-production strategy, whereby public services offered at the institution would focus on making use of resources through community building, collaboration, and resource sharing. In this context, “governance” refers to the role of multi-stakeholders involved in decision making, autonomy, leadership, and accountability. The effectiveness and success of this cybernetic governance depends on the institution community; the board, Vice-Chancellor, university management committee, Deans and Directors involved. The main idea is to analyse cybernetic governance as a model for processing information and a platform for co-production on governance empowerment at higher education institutions in Malaysia. Hence literatures are reviewed to apply the concepts to this research. An expected outcome of this research would be the evidence to improve policy performance in governance arrangements. Therefore, cybernetic governance contribution is the practice of good governance for intelligent institutions.